2011
DOI: 10.1371/journal.pone.0016882
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Carboplatin and Paclitaxel as First- and Second-Line Treatment in 61 Patients with Metastatic Melanoma

Abstract: BackgroundPatients with metastatic melanoma have a very unfavorable prognosis with few therapeutic options. Based on previous promising experiences within a clinical trial involving carboplatin and paclitaxel a series of advanced metastatic melanoma patients were treated with this combination.MethodsData of all patients with cutaneous metastatic melanoma treated with carboplatin and paclitaxel (CP) at our institution between October 2005 and December 2007 were retrospectively evaluated. For all patients a once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…This said, it is difficult to separate the effect of CP-870,893 on tumor responses from that of chemotherapy, because the combination of carboplatin and paclitaxel are known to exert antitumor activity against the neoplasms represented in our cohort. For example, in two recent studies enrolling patients with advanced melanoma (a Phase II study with 61 patients 9 and a Phase III study with 135 patients on the carboplatin/paclitaxel/placebo arm 10 ), objective tumor response rates to carboplatin and paclitaxel (given every 21 d) ranged from 4.9% to 11%. A previous smaller study of 15 patients documented an objective PR rate of 20% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This said, it is difficult to separate the effect of CP-870,893 on tumor responses from that of chemotherapy, because the combination of carboplatin and paclitaxel are known to exert antitumor activity against the neoplasms represented in our cohort. For example, in two recent studies enrolling patients with advanced melanoma (a Phase II study with 61 patients 9 and a Phase III study with 135 patients on the carboplatin/paclitaxel/placebo arm 10 ), objective tumor response rates to carboplatin and paclitaxel (given every 21 d) ranged from 4.9% to 11%. A previous smaller study of 15 patients documented an objective PR rate of 20% 11 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, results of a phase II trial and a retrospective review showed that PC was associated with an objective response rate (ORR) of B20-25% [14,15]. Moreover, another retrospective study showed that first-line or second-line PC improved OS and ORR in patients with advanced metastatic cutaneous melanoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally we observed that PLX4720 was highly synergistic with paclitaxel. This combination represents a potentially impactful combination since paclitaxel and vemurafenib are both used in clinical trials for the treatment of melanoma [3, 14]. Furthermore previous reports have suggested that the combination of BRAF inhibitors with paclitaxel represents a promising therapeutic approach for overcoming resistance in BRAF melanomas [15].…”
Section: Resultsmentioning
confidence: 99%